Komparasi Kinerja Keuangan Bank Umum Syariah dengan Pendekatan RGEC dan Islamicity Performance Index - Tiara Putie Purwitasari; Fifi Afiyanti Tripuspitorini; Eni Endaryati; Vivi Kumalasari Subroto (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
This study aims to compare the financial performance of Islamic Commercial Banks calculated using the disclosure of materialistic and spiritual values using the RGEC method and the Islamicity Performance Index for the 2016 – 2020 period. Using secondary data, namely the 2016 – 2020 annual financial statements of Islamic banks which have been published on the website an official from each bank. The population in this study is Islamic Commercial Banks taking 12 (twelve) BUS with purposive sampling technique. This research is quantitative comparative research by processing data from the annual financial statements, then explained descriptively. Using 4 indicators from RGEC, namely Risk Profile, Good Corporate Governance, Earnings, and Capital, and 4 indicators from the Islamicity Performance Index, namely Profit Sharing Ratio (PSR), Zakat Performance Ratio (ZPR), Equitable Distribution Ratio (EDR), and Islamic Income vs. Non - Islamic Income. The results of data analysis, it can be concluded that the results of the financial performance of BUS with the RGEC approach are included in the fairly healthy category. While the results of the financial performance of BUS with the Islamicity Performance Index approach are included in the unsatisfactory category. Based on statistical tests, there are differences in the results of the soundness of financial performance when viewed from the RGEC and Islamicity Performance Index approaches.